Literacy development for 21st century: a review of Indonesian freedom of learning curriculum in elementary school - Muzaki, Ferril Irham (Universidad de Jaén, 2023)
In the "knowledge society", the huge impact of advanced information and communication technology (ICT) on the lives of individuals and societies gives rise to the need to change the perspective of current literacy and identify and define relevant new literacy. In this article, seven literacies related to multimodal information processing, navigation in the information space, interpersonal communication, visual literacy, hyperrational, personal information management and overcoming complexity will be defined and discussed. Reading is a complex activity that requires modern coordination and simultaneous performance of various skills. With the help of simultaneous demonstration of coordinated skills, we acquire fluency expressed in sufficient reading speed that passes easily, excessive mind control and purposeful attention. Reading comprehension and learning from the text are the core of reading in schools. It deals with reading ability, proficiency in language subjects and general fluency. Among the most important aspects of reading comprehension are the reader's metacognitive abilities and reading strategies, the use of knowledge that the reader has had before, and their motivation.